Definitions of genetic testing in European legal documents - Varga, Orsolya (Springer-Verlag, 2012)
The definition of “genetic testing” is not a simple matter, and the term is often used with different meanings. The purpose of this work was the collection and analysis of European (and other) legislation and policy instruments regarding genetic testing, to scrutinise the definitions of genetic testing therewith contained the following: 60 legal documents were identified and examined—55 national and five international ones. Documents were analysed for the type (context) of testing and the material tested and compared by legal fields (privacy and confidentiality, data protection, biobanks, insurance and labour law, forensic medicine); some instruments are very complex and deal with various legal fields at the same time. There was no standard for the definitions used, and different approaches were identified (from wide general, to some very specific and technically based). Often, legal documents did not contain any definitions, and many did not distinguish between genetic testing and genetic information. Genetic testing was more often defined in non-binding legal documents than in binding ones. Definitions are core elements of legal documents, and their accuracy and harmonisation (particularly within a particular legal field) is critical, not to compromise their enforcement. We believe to have gathered now the evidence for adopting the much needed differentiation between (a) “clinical genetics testing”, (b) “genetics laboratory-based genetic testing” and (c) “genetic information”, as proposed before. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12687-012-0077-1) contains supplementary material, which is available to authorized users.